Chiral all-dielectric trimer nanoantenna. (March 2018) - Ullah, Kaleem; Garcia-Camara, Braulio; Habib, Muhammad; Liu, Xuefeng; Krasnok, Alex; Lepeshov, Sergey; Hao, Jingjing; Liu, Juan; Yadav, N. P
Highlights: All dielectric chiral nanotrimer structure composed of three spheres of the Cu2 O material of different sizes is proposed. We have successfully measured and verified it numerically that our structure exhibit chirality and due to Mie resonance, its chirality can be enhanced, in particular, we studied chirality due to the enhancement of magnetic resonances in our proposed geometry. We measured the near-field peculiarities of the proposed nanoantenna, the ability of changing the nanoantenna near field scattering by varying the light polarization is shown. Abstract: Chirality is a property of certain molecules, materials or artificial nanostructures, which enables them to interact with the spin angular momentum of an incident light. This provides a different optical response, depending on the incident polarization, which gives rise to chiral optical spectroscopies. However, low-detection limits require an enhanced chiral light-matter interaction. Here, we propose a novel type of resonant chiral optical nanoantenna based on high-index dielectric (Cu2 O) spherical nanoparticles arranged in a trimer geometry. We demonstrate both numerically and experimentally that this trimer nanoantenna exhibits resonantly enhanced optical dichroism and light hotspots, which are associated with this geometry. Moreover, we apply near-field optical microscopy to measure the near-field peculiarities of the proposed nanoantenna. The ability of changing the nanoantenna near field scattering by varying the light polarization is shown.